A Forgotten Guidewire: Complication of Central Venous Catheterization - Funda Gümüş; Hacer Yeter; Melahat Karatmanlı Erol; Nalan Şanlı; Berk Özkaynak; Ayşin Alagöl (Galenos Yayinevi, 2011)
Central venous catheterization is an invasive procedure commonly preferred for hemodynamic monitorization, total parenteral nutrition, cardiac pacemaker implantation, long-term use of vasoactive or irritating agents and hemodialysis. We present a 19-year-old woman with acute renal failure scheduled for hemodialysis catheterization. A catheter guidewire extending from the right internal jugular vein to the right external iliac vein was detected in the chest X-ray, taken two hours following catheterization after occurrence of arrhythmia and hypotension. Catheteter guidewire was extracted noninvasively without any complications. Most common reasons for this complication are stated to be attention deficits, lack of experience, overtired staff, and inadequate supervision of trainees. In this paper, we discussed this complication's causes and preventive methods. (Journal of the Turkish Society Intensive Care 2011; 9:64-7)